Penerapan Algoritma Semut Dalam Penentuan Distribusi Jalur Pipa Pengolahan Air Bersih - Windarto, Agus Perdana; Sudirman, Sudirman (JSINBIS (Jurnal Sistem Informasi Bisnis), 2018)
In general, the shortest path search can be divided into two methods, namely conventional methods and heuristic methods. Conventional methods tend to be more easily understood than heuristic methods, but when compared to the results obtained, heuristic methods are more varied and the time required for calculation is shorter. In the heuristic method there are several algorithms, one of which is the ant algorithm. An ant algorithm is an algorithm that is adopted from the behavior of ant colonies. Naturally ant colonies are able to find the shortest route on the way from the nest to the food sources. Ant colonies can find the shortest route between the nest and the source of food based on footprints on the trajectory that has been passed. The more ants that pass through a path, the more obvious the footprints will be. Ants Algorithms are very appropriate to be applied in solving optimization problems, one of which is to determine the shortest path. This study aims to facilitate the Development of Drinking Water Treatment Performance to make decisions in determining the point where the installation of water distribution pipelines that will be distributed to residents' homes. This study took 8 points of clean water treatment pipeline with starting point A and point N. Based on the calculation of clean water pipeline between A and N by using ant algortima, from two cycles passed, it is proven that the shortest path is only one pipeline, pipe N as destination with route length 4 as V1 → V2 → V3 → V4 → V8.